A survey of educational uses of molecular visualization freeware. Issue 3 (4th May 2013) - Craig, Paul A.; Michel, Lea Vacca; Bateman, Robert C.
<x xml:space="preserve">Abstract</x> As biochemists, one of our most captivating teaching tools is the use of molecular visualization. It is a compelling medium that can be used to communicate structural information much more effectively with interactive animations than with static figures. We have conducted a survey to begin a systematic evaluation of the current classroom usage of molecular visualization. Participants (n = 116) were asked to complete 11 multiple choice and 3 open ended questions. To provide more depth to these results, interviews were conducted with 12 of the participants. Many common themes arose in the survey and the interviews: a shared passion for the use of molecular visualization in teaching, broad diversity in software preference, the lack of uniform standards for assessment, a desire for more quality resources, and the challenge of enabling students to incorporate visualization in their learning. The majority of respondents had used molecular visualization for more than 5 years and mentioned 32 different visualization tools used, with Jmol and PyMOL clearly standing out as the most frequently used programs at the present time. The most common uses of molecular visualization in teaching were lecture and lab illustrations, followed by exam questions, in‐class or in‐laboratory exercises, and student projects, which frequently included presentations. While a minority of instructors used a grading rubric/scoring matrix for assessment of student learning with molecular visualization, many expressed a desire for common use assessment tools. © 2013 by The International Union of Biochemistry and Molecular Biology, 41(3):193–205, 2013